Stable gas-in-liquid emulsions : production in natural waters and artificial media - D'Arrigo, Joseph S. (Studies in interface science, 2003)
This title is a greatly expanded and updated second edition of the original volume published by Elsevier in 1986. New material has been integrated with the original content in an organized and comprehensive manner. Five new chapters have been included, which review over one and a half decades of research into lipid-coated microbubbles (LCM) and their medical applications. The new chapters contain much experimental data, which is examined in detail, along with relevant current literature. This current edition builds on the original work in effectively filling the gap in the market for a comprehensive account of the surfactant stabilization of coated microbubbles. - Presents updated results from extensive multidisciplinary research on coated microbubbles - Greatly expanded and updated 2nd edition, with five new chapters - Fills the gap for a comprehensive and up-to-date account of subject matter.